HUBUNGAN PENINGKATAN ANTIBODY Ig A ANTI EA EBV PADA PASIEN PENDERITA KNF PADA SUKU NIAS - Ginting, Hana Isal Salina (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Nasopharyngeal carcinoma (NPC) is a malignant tumor of the head and neck region, predominantly found in Southeast Asia, and is closely associated with Epstein–Barr Virus (EBV) infection. Detection of Immunoglobulin A (IgA) antibodies against the Early Antigen (EA) of EBV has been recognized as a potential non-invasive biomarker for early diagnosis. Genetic, environmental, and lifestyle factors — including the traditional habit of consuming preserved foods among the Nias ethnic group — are believed to influence the antibody response. This study aimed to analyze the association between elevated IgA anti-EA EBV antibody levels and the occurrence of NPC among Nias patients. An observational analytic study with a case–control design was conducted involving 29 NPC patients and 29 healthy Nias individuals as controls. Serum samples were examined serologically at the Integrated Laboratory, Faculty of Medicine, University of North Sumatra. Data were analyzed using the Chi-square and Mann–Whitney tests. The findings revealed that the mean level of IgA anti-EA EBV antibodies in NPC patients (246.22 ± 320.05 U/mL) was significantly higher than that of healthy controls (51.79 ± 1.55 U/mL) (p < 0.05). Positive serological reactivity was detected in 55.2% of NPC patients compared to 10.3% in the control group. No significant associations were found between age or gender and the serological results (p > 0.05). These results indicate that elevated IgA anti-EA EBV antibody levels may serve as an important immunological marker for early detection of NPC, particularly among high-risk populations such as the Nias ethnic group.